Personalization and Customer Relationship Management in the Context of Internet Banking - Raine, Pauliina (My University, 2005)
For service companies with presences on the Internet, customer relationships and their management has become critical for the business success. Customer needs have become more sophisticated, and they want personal service, also on the Internet. Therefore companies need to be customer-oriented and find ways to use the Internet to produce personalized service and consequently increase customer satisfaction and loyalty. In this study, personalization as a part of customer relationship management is examined in the context of Internet banking. The study aims at increasing understanding of how personalization has been and can be used for the purposes of customer relationship management in Internet banking. In addition, motives for service personalization are discussed. This study also briefly examines different techniques of personalization of electronic service offerings, and presents scenarios about the future of personalization. The empirical part of this thesis is conducted as a case study. Eight specialists from the expertise areas of Internet banking and personalization were interviewed. The purpose is to build understanding of how personalization is utilized in one Nordic Internet bank and what are the effects of personalization on customer relationships. The analysis of interviews also illustrates how the utilization of personalization of Internet banking services is expected to develop in the following years. The results of this study indicate that, despite of the positive benefits of personalization, so far the use of service personalization in Internet banking context has been limited and utilized personalization techniques are quite simple. The effects of personalization are believed to be positive for both the bank and its customers. However, due to the limited usage of personalization, there are no measures about the concrete effects on customer relationships. However, banks are currently allocating resources on developing these services and therefore the utilization of personalization is likely to increase significantly in the near future.
Keywords: personalization; customer relationship management; eCRM; Internet banking; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|